The Effect of Leverage on Stock Prices is Moderated by Liquidity in Food and Beverage Subsector Companies on the Indonesia Stock Exchange - Rosmayani; Syamsul Ridjal; Edy Jumady (Enrichment : Journal of Management, 2022)
This study aims to examine and analyze the effect of leverage on stock prices moderated by liquidity in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. Data collection uses secondary data, namely the company's financial statements for the 2018-2021 period using purposive sampling technique with 10 companies so that 40 samples are obtained. The results of these financial statements have been tested for classical assumptions, linear regression tests and Moderated Regression Analysis (MRA). The results showed that the first, second, and third hypotheses were rejected because leverage and liquidity had no partial effect on stock prices and liquidity was unable to moderate the effect of leverage on stock prices. Meanwhile, the fourth hypothesis is accepted because leverage and liquidity have no simultaneous effect on stock prices.